Crystallite Size and Microstrain Measurement of Cathode Material after Mechanical Milling using Neutron Diffraction Technique - A. Fajar; Gunawan Gunawan; E. Kartini; H. Mugirahardjo; M. Ihsan (Atom Indonesia, 2010)
The measurements of neutron diffraction patterns of commercially product and 10 hour mechanically milled cathode material lithium cobaltites (LiCoO2) have been performed. Rietveld analysis using FullProf does not show the change of crystal structure due to milling process, but the diffraction pattern has a lower intensity and the diffraction-line was broadening. The results of line-broadening study on milled sample using Rietveld methods detected that the microstrain was occurred in the sample with value 0.127080(35) % and the average crystallite size was 424.78(20) Å.Received: 7 October 2010; Revised: 31 October 2010; Accepted: 1 November 2010